Optimasi Penggunaan Bio-Pestisida sebagai Pengganti Pestisida Kimia pada Pertanian di Kec. Percut Sei Tuan, Kab. Deli Serdang - Sitompul, Delon; Lumbantobing, Putri; Manik, Suandro; Harefa, Meilinda Suriani (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Deli Serdang is an agricultural center in North Sumatra where farming activities are still done conventionally using chemical fertilizers and synthetic pesticides. The frequent use of synthetic pesticides continuously leads to negative impacts such as the emergence of pest resistance and resurgence. Because the pests have become resistant, farmers will continue to use synthetic pesticides by increasing the dosage and application time so that production can be achieved. The purpose of this research is to understand the actual impact, identify sustainable solutions, and promote agriculture that is safer, environmentally friendly, and sustainable. By analyzing the impact of pesticide use in agriculture considering various aspects. The method used is qualitative descriptive through interviews and observations. The excessive use of pesticides in agricultural ecosystems pollutes the soil and water and kills beneficial non-target organisms, which can disrupt the ecosystem balance and reduce agricultural biodiversity. Meanwhile, the impact on the health of farmers includes health risks, including acute and chronic poisoning. Farmers and agricultural workers may experience respiratory problems, skin irritation, nervous system damage, and long-term risks such as cancer.